Empowering Ethiopian Smallholder Farmers: Lersha-CIMMYT Collaboration under AICCRA Initiative for Tailored Agro-Climate Advisory towards building smallholder farmers' Resilience - Sileshi, Meron; Endris, Hanna; Nassir, Abdelah; Tadesse, Noha; Yohannes, Zemen; Endrias, Abrhame (Green Agro Solution PLC, 2024)
Lersha is an inclusive one-stop digital service that aims to support smallholder farmers by providing them with convenient access to essential resources and assistance for their agricultural needs. Leveraging technology, Lersha offers a comprehensive platform where farmers can also directly connect with Lersha Agents to fulfil their farming requirements.